2020
DOI: 10.1074/jbc.ra120.014280
|View full text |Cite
|
Sign up to set email alerts
|

Shared requirements for key residues in the antibiotic resistance enzymes ErmC and ErmE suggest a common mode of RNA recognition

Abstract: Erythromycin resistance methyltransferases are S-adenosyl methionine dependent Rossmann-fold methyltransferases that convert A2058 of 23S rRNA to m62A2058. This modification sterically blocks binding of several classes of antibiotics to 23S rRNA, resulting in a multi-drug resistant phenotype in bacteria expressing the enzyme. ErmC is an erythromycin resistance methyltransferase found in many Gram-positive pathogens while ErmE is found in the soil bacterium that biosynthesizes erythromycin. Whether ErmC and Erm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…While several positively-charged sites proved to be essential for methylation activity, mutation of these sites individually did not cause significant changes in binding affinity for the RNA substrate. Such a disconnect between enzyme activity and RNA binding affinity was observed in ErmE (24) and is analogous to the lack of correlation between binding affinity and specificity for aptamers (25). Maravic et al also described an E. coli strain carrying ErmC gene with a R134A mutation (equivalent to R141A of Erm38) that resulted in complete loss of erythromycin resistance, while mutations R112A and K133A in ErmC (equivalent to R119A and R140A of Erm38) reduced erythromycin resistance (26).…”
Section: Discussionmentioning
confidence: 93%
“…While several positively-charged sites proved to be essential for methylation activity, mutation of these sites individually did not cause significant changes in binding affinity for the RNA substrate. Such a disconnect between enzyme activity and RNA binding affinity was observed in ErmE (24) and is analogous to the lack of correlation between binding affinity and specificity for aptamers (25). Maravic et al also described an E. coli strain carrying ErmC gene with a R134A mutation (equivalent to R141A of Erm38) that resulted in complete loss of erythromycin resistance, while mutations R112A and K133A in ErmC (equivalent to R119A and R140A of Erm38) reduced erythromycin resistance (26).…”
Section: Discussionmentioning
confidence: 93%
“…In an in vitro setting, chimera’s which consisted of loop1 and loop12 of Erm onto an otherwise KsgA scaffold made it capable of methylating Erm mini-RNA substrates . Furthermore, saturation mutagenesis of loop12 also confirmed that positively charged residues in loop12 of Erm are important for substrate recognition . Thus, it appears that these important loop elements are crucial in tunning specificity.…”
Section: Discussionmentioning
confidence: 90%
“…22 Furthermore, saturation mutagenesis of loop12 also confirmed that positively charged residues in loop12 of Erm are important for substrate recognition. 49 Thus, it appears that these important loop elements are crucial in tunning specificity. The 30S−KsgA cryo-EM structure shows that loop 12 and another loop14 that resides in the C-terminal head domain serving as anchor points via interaction with the peripheral RNA segments provide an additional layer of stringency to the recognition process.…”
Section: ■ Discussionmentioning
confidence: 99%
“…To corroborate the fact that these loops indeed tune specificity, an earlier study showed that chimera’s which consisted of loop1 and loop12 of Erm onto an otherwise KsgA scaffold made it capable of methylating Erm mini-RNA substrates (Bhujbalrao & Anand, 2019). Furthermore, saturation mutagenesis of loop12 also confirmed that positively charged residues in loop12 of Erm are important for substrate recognition (Rowe, Mecaskey et al, 2020).…”
Section: Discussionmentioning
confidence: 90%